Multiple organ dysfunction syndrome after multiple trauma. - Walsh CR (Orthopaedic Nursing)
Multiple organ dysfunction syndrome (MODS) is a serious, often fatal, sequel to multiple trauma. Prolonged shock states, severe sepsis, acute pancreatitis, acute renal failure, severe burns, ischemic conditions, and acute respiratory distress syndrome have been implicated in the development of MODS. Despite advances in critical care therapies and infection control practices, severe sepsis remains a major health problem, with an estimated mortality rate of 30-50% (Ely, Kleinpell, & Goyette, 2003). The purposes of this article are to describe the pathophysiologic changes that lead to the development of MODS and discuss strategies to prevent the development of MODS and to treat MODS if it develops.